Chemical and Mechanical Properties of Cuticular Membranes Isolated from Young Matured Leaves of Sonneratia alba - Yuki Takahashi; Shuntaro Tsubaki; Masahiro Sakamoto; Shin Watanabe; Wahyu Dwianto; Jun-ichi Azuma (Wood Research Journal, 2011)
Leaf cuticular membranes (CMs) of Sonneratia alba are considered to play an important role in environmental tolerance, and chemical and mechanical properties of their CMs are crucial factors which provide protective barrier and mechanical supports.  Leaf CMs were enzymatically isolated from both adaxial and abaxial sides of young matured leaves (L3), and their chemical and mechanical properties were compared. Chemical compositions of both CMs were similar reflecting their morphological similarity.  The adaxial CM was consisted of 23.4% wax, 64.2% cutin, 7.4% cutan and 6.1% polysaccharides with thickness of 9 µm, and the abaxial CM had the values of 23.9%, 63.2%, 9.4%, 4.2% and 8 µm, respectively.  Major monomers in both cutins were 9,10-epoxy-18-hydroxyoctadecanoic acid and 9(10),16-dihydroxyhexadecanoic acid.  Mechanical properties of both CMs were also similar reflecting their morphological and chemical compositional similarities.